Experimental and numerical investigation of nitrogen oxides reduction in diesel engine selective catalytic reduction system. (1st April 2022) - Kurzydym, Damian; Żmudka, Zbigniew; Perrone, Diego; Klimanek, Adam
Highlights: An experimental study was carried out for the original and replacement SCR systems for deNOx. A new urea-water solution mixer was designed and tested. Laser scanning was used to determine numerical representation of the SCR geometry. CFD model of the SCR system was developed, validated, and successfully used. A reduced NOX emission and increased NH3 slip were observed for the replacement part. Abstract: The article presents an experimental and numerical study of nitrogen oxides reduction in diesel car selective catalytic reduction (SCR) system. Due to increasingly stringent emission standards, SCR systems have recently been installed in diesel cars around the world. The system under investigation is a recently developed replacement part dedicated for secondary market (aftermarket). The analysis includes the whole aftertreatment system, i.e. the urea injection, the mixer and two-stage SCR system, and is aimed at meeting the desired performance and requirements of the European emission standards. Within the experimental work various design variants of the SCR system and mixers at different operational parameters were studied. Several solutions were investigated under conditions that reflected the real operating conditions of the diesel engine operation. Among other things, pressure drops on monoliths, gas distribution and conversion of nitrogen oxides were tested and analyzed. Furthermore, for the purpose of numerical model development, laser scanning was used to extract 3D models of the real geometries of the system elements. A commercial code ANSYS Fluent was used to perform the multiphase computational fluid dynamics studies, in which the urea-water solution droplets were tracked in a Lagrangian frame of reference and the catalysts, were treated as porous media. Attention was given to the implementation of the SCR reaction kinetics. The developed model, with implemented kinetics, was verified by comparing the results of numerical calculations with the analytical solution. The CFD model was then validated against the experimental data showing good agreement between the measured and simulated parameters. The final design of the replacement part was compared with an original system delivered by original equipment manufacturer (OEM) for this engine. It was found that application of the new mixer and separated SCR converters of the replacement part led to slightly lower NOX emission, and increased NH3 slip and pressure drop, but kept on acceptable level.